Minimally important differences for subjective improvement in postural stability in patients with bilateral vestibulopathy. (16th March 2021) - Fujimoto, Chisato; Kawahara, Takuya; Kinoshita, Makoto; Ichijo, Kentaro; Oka, Mineko; Kamogashira, Teru; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Highlights: The degree of clinically meaningful postural improvement is still unknown. Minimally important difference in posture in bilateral vestibulopathy is estimated. Minimally important difference is useful in interpreting the clinical trials. Abstract: Objective: To determine minimally important differences (MIDs) for subjective improvement in postural stability after a therapeutic intervention in patients with bilateral vestibulopathy (BVP). Methods: Thirteen BVP patients received noisy galvanic vestibular stimulation (nGVS) for 30 min and their static posture with eyes closed was monitored after the stimuli. The velocity of the center of pressure (COP) movement, the area enclosed by the COP movement, and the root mean square (RMS) of the displacement of the COP were measured for 30 s. Subjective evaluation of postural stability after nGVS was graded as worsened, slightly worsened, unchanged, slightly improved and improved in comparison with postural stability measured without nGVS. Anchor-based methods were used to estimate MIDs for subjective improvement. Velocity, area and RMS for each anchor-response group were averaged (2 sessions, each with 5 measurement periods during 3 h after the stimuli). The mean changes between the slightly improved group and unchanged group were used as estimates for MID for improvement. Results: A total of 129 anchors were analyzed. Subjective evaluations numbered 83 (64%) for unchanged and 33 (26%) for slightly improved. Anchor-based methods yielded estimates for MIDs of -0.43 cm/s in velocity improvement ( p  < 0.01), -0.77 cm 2 for area improvement ( p  < 0.01) and -0.23 cm for RMS improvement ( p  < 0.001). Conclusion: The present study provides the estimation of MIDs for improving postural stability in BVP patients and may be useful for interpreting whether the results from clinical trials are meaningful in future studies.